Understanding the Effect of Crystalline Structural Transformation for Lead‐Free Inorganic Halide Perovskites - Shi, Ming; Li, Guanna; Tian, Wenming; Jin, Shengye; Tao, Xiaoping; Jiang, Yiming; Pidko, Evgeny A.; Li, Rengui; Li, Can (Advanced materials (Weinheim), 2020)
Lead‐free inorganic halide perovskites have triggered appealing interests in various energy‐related applications including solar cells and photocatalysis. However, why perovskite‐structured materials exhibit excellent photoelectric properties and how the unique crystalline structures affect the charge behaviors are still not well elucidated but essentially desired. Herein, taking inorganic halide perovskite Cs3Bi2Br9 as a prototype, the significant derivation process of silver atoms incorporation to induce the structural transformation from Cs3Bi2Br9 to Cs2AgBiBr6, which brings about dramatic differences in photoelectric properties is unraveled. It is demonstrated that the silver incorporation results in the co‐operated orbitals hybridization, which makes the electronic distributions in conduction and valence bands of Cs2AgBiBr6 more dispersible, eliminating the strong localization of electron–hole pairs. As consequences of the electronic structures derivation, exhilarating changes in photoelectric properties like band structure, exciton binding energy, and charge carrier dynamics are verified experimentally and theoretically. Using photocatalytic hydrogen evolution activity under visible light as a typical evaluation, such crystalline structure transformation contributes to a more than 100‐fold enhancement in photocatalytic performances compared with pristine Cs3Bi2Br9, verifying the significant effect of structural derivations on the exhibited performances. The findings will provide evidences for understanding the origin of photoelectric properties for perovskites semiconductors in solar energy conversion. Incorporating silver atoms into the inorganic halide perovskite Cs3Bi2Br9 to form Cs2AgBiBr6 eliminates the strong localization of electron–hole pairs, makes the electronic band distribution more dispersible, and further changes the photoelectric properties including band structure, exciton binding energy, charge carrier mobility, and carrier relaxation lifetime, leading to a remarkable enhancement in photocatalytic hydrogen evolution under visible light.